2019
DOI: 10.1536/ihj.18-012
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Processing in Patients with and Without Left Ventricular Dysfunction

Abstract: This study aimed to examine the relationship between corin expression and circulating brain natriuretic peptide in patients with left ventricular (LV) dysfunction. Circulating levels of B-type natriuretic peptide (BNP) can be an indicator of LV dysfunction. The 32amino-acid BNP is cleaved by corin, a cardiac serine protease, from its108-amino-acid pro-brain natriuretic peptide (proBNP) precursor. This study included 25 patients with idiopathic dilated cardiomyopathy (DCMP) and LV dysfunction and 44 heart trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Importantly, we found that cardiac-specific expression of catalytically active corin delays the onset of symptomatic HFrEF associated with lung edema and extends life in experimental mouse model of DCM [16,17]. In agreement with our results, corin cardiac transcript levels were upregulated in heart transplant recipients with normal left ventricular (LV) function in comparison with DCM/HFrEF patients [24]. These results suggested that preservation or restoration of cardiac corin levels might delay the progression of HFrEF.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Importantly, we found that cardiac-specific expression of catalytically active corin delays the onset of symptomatic HFrEF associated with lung edema and extends life in experimental mouse model of DCM [16,17]. In agreement with our results, corin cardiac transcript levels were upregulated in heart transplant recipients with normal left ventricular (LV) function in comparison with DCM/HFrEF patients [24]. These results suggested that preservation or restoration of cardiac corin levels might delay the progression of HFrEF.…”
Section: Introductionsupporting
confidence: 90%
“…Converging lines of evidence from clinical and translational studies have shown that genetic abnormalities and reduction in corin cardiac expression level negatively affect DCM and HFrEF outcomes. Cardiac transcripts and circulating levels of corin are depressed in patients and translational animal models with DCM and HFrEF [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]35,36,51], and are pathologically modulated in DCM before the onset of edema and other clinical signs and symptoms of HFrEF [22,23]. In a translationally relevant mouse model of DCM-HFrEF with reduced cardiac and plasma corin levels, we reported that genetic restoration of cardiac-specific catalytically active, native corin improved systolic function, reduced myocardial fibrosis, decreased edema, and prolonged survival [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-pro BNP was processed into proBNP (108 amino acids) and subsequently proBNP was cleaved into NT-ProBNP (76 amino acids) and BNP (32 amino acid). 26,27) NT-proBNP and BNP share a common mechanism of clearance through the glomerulus. In patients with a normal or mildly decreased glomerular filtration rate (GFR), the molar ratio of NT-proBNP to BNP must be 1.0 or less because both peptides are cleared at about the same rate and have similar half-lives.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of corin seems more important in HF. HF is associated not only with reduced plasma corin levels (16,17,24) and decreased myocardial CORIN expression (25), but also with impaired cleavage of pro-ANP (17). In mice with progressive dilated or ischemic cardiomyopathy, restoration of suppressed cardiac corin expression levels reduces myocardial fibrosis, improves contractile function, reduces alveolar edema and congestion, and attenuates heart failure (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%